TRANSFORMING ISLAMIC EDUCATION MANAGEMENT IN EMPOWERING SUSTAINABLE EDUCATION IN SOCIETY 5.0 - Akhyar, Yundri; Ningsih, wirda (Universitas Muhammadiyah Mataram, 2024)
Abstrak: Di era Society 5.0, dimana teknologi dan masyarakat menyatu, manajemen pendidikan Islam memainkan peran penting dalam mendorong pendidikan berkelanjutan. Untuk menyelaraskan ajarannya dengan tujuan pendidikan berkelanjutan di Society 5.0, institusi pendidikan Islam harus mengalami perubahan transformasional. Penelitian ini bertujuan untuk mengetahui strategi transformasi manajemen pendidikan untuk mendukung pendidikan berkelanjutan di era Society 5.0. Penelitian ini menggunakan metodologi penelitian kepustakaan. Hasil penelitiannya adalah manajemen pendidikan Islam harus bertransformasi dalam Integrasi Teknologi, Kurikulum dengan Pendekatan Holistik, Mengembangkan Keterampilan Pemecahan Masalah dan Berpikir Kritis, serta Keterlibatan Masyarakat dan Pembelajaran berbasis Pengabdian.Abstract: In the age of Society 5.0, when technology and society intersect, the management of Islamic education plays a vital role in advancing sustainable education. In order to harmonize their teachings with the objectives of sustainable education in Society 5.0, Islamic educational institutions must undertake transformative reforms. The research seeks to identify the strategy for transforming education management in order to facilitate sustainable education in the era of Society 5.0. The study employed a library-based research methodology. The findings of the study indicate that Islamic education management should undergo transformation in several areas, namely Technology Integration, Curriculum with a Holistic Approach, Developing Problem-Solving and Critical Thinking Skills, and Community Engagement and Service-Learning.